2016
DOI: 10.1002/term.2116
|View full text |Cite
|
Sign up to set email alerts
|

Efficient cryopreservation of human mesenchymal stem cells using silkworm hemolymph-derived proteins

Abstract: Cryopreservation methods for human mesenchymal stem cells (hMSCs) typically depend on the presence of fetal bovine serum (FBS) with dimethyl sulphoxide (DMSO), which is not appropriate for therapeutic applications. In our previous study, we found that storage protein 2 (SP2), a natural material derived from silkworm hemolymph, has an inhibitory effect on the generation of reactive oxygen species (ROS). In this study, we used SP2 as an alternative to establish an effective, low-DMSO and FBS-free cryopreservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Had we conducted the cryopreservation in a liquid nitrogen tank for longer durations, our outcomes might have been different. Kim et al reported that the viability of human umbilical cord MSCs cryopreserved in a liquid nitrogen tank for 1 year was comparable to that of cells cryopreserved for 7 days [37]. Abbruzzese at al.…”
Section: Discussionmentioning
confidence: 99%
“…Had we conducted the cryopreservation in a liquid nitrogen tank for longer durations, our outcomes might have been different. Kim et al reported that the viability of human umbilical cord MSCs cryopreserved in a liquid nitrogen tank for 1 year was comparable to that of cells cryopreserved for 7 days [37]. Abbruzzese at al.…”
Section: Discussionmentioning
confidence: 99%
“…A longer period of cryopreservation could lead to different results. However, the viability of human umbilical cord MSCs cryopreserved for 1 year was comparable to that of cells cryopreserved for 7 days [31], suggesting that the results would not change even if the synovial MSCs were cryopreserved for 1 year.…”
Section: Discussionmentioning
confidence: 94%
“…1 a Schematic diagram for two types of cryoinjuries occurring during cryopreservation of cells; b schematic diagram for various biotechnology techniques used in cryopreservation and their method of protection extracellular cryopreservation. However, FBS is derived from animals and has risk of inducing viral infections and immunogenicity inpatients [20,21].…”
Section: Introductionmentioning
confidence: 99%